2022
DOI: 10.3389/fnagi.2022.919712
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Genotype e2: Neuroprotection and Its Limits

Abstract: In this review, we comprehensively, qualitatively, and critically synthesized several features of APOE-e2, a known APOE protective variant, including its associations with longevity, cognition, and neuroimaging, and neuropathology, all in humans. If e2’s protective effects—and their limits—could be elucidated, it could offer therapeutic windows for Alzheimer’s disease (AD) prevention or amelioration. Literature examining e2 within the years 1994–2021 were considered for this review. Studies on human subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 146 publications
1
12
1
Order By: Relevance
“…In our analyses, sex × APOE effects on cognition were generally strengthened after ε2/ε4 genotype removal. These results are in line with previous studies, which have reported as much as a 3-fold increase in the odds of developing AD for those with the ε2/ε4 genotype . We also conducted age-stratified sensitivity analyses to determine if significant sex × APOE interactions on cognition differed between participants younger than 75 years and participants 75 years or older at baseline.…”
Section: Discussionsupporting
confidence: 85%
“…In our analyses, sex × APOE effects on cognition were generally strengthened after ε2/ε4 genotype removal. These results are in line with previous studies, which have reported as much as a 3-fold increase in the odds of developing AD for those with the ε2/ε4 genotype . We also conducted age-stratified sensitivity analyses to determine if significant sex × APOE interactions on cognition differed between participants younger than 75 years and participants 75 years or older at baseline.…”
Section: Discussionsupporting
confidence: 85%
“…Controversially, Shinohara et al, (2020) showed that APOEε2 accelerates cognitive decline in diabetic patients by 4 years. This could be explained by the synergic effect between diabetes ( Hardigan et al, 2016 ; Peng et al, 2021 ) and the APOEε2 genotype in enhancing neurovascular impairment and tauopathies ( Kim et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reports of associations of ε2 with cognitive function however have largely been inconsistent due to different study designs and small samples of ε2 carriers (Kim et al, 2022). At least one study reported ε2 carriers had better verbal memory and fluency, but only in women.…”
Section: Deficits In Executive Function Have Been Observed In Personsmentioning
confidence: 99%